Labour's First Year : 1945-46 (London : Common Wealth Publications Committee, 1946)
1946 1946 1940s 27 pages Criticisms (a) CONSERVATIVE. The British Medical Association whose attitude is reflected in the utterances of the Conservative Party, has declared that it opposes on principle any plan which :— 1. Leads directly or indirectly to the profession as a whole becoming full-time salaried servants of the State or local authorities. 2. Interferes with the freedom of doctors to choose the form, place and type of work they prefer without governmental or other direction. 3. Takes away from doctors the right to buy or sell the goodwill of practices. To label the doctors as reactionaries without trying to understand what lies at the root of their declared opposition is to be foolishly superficial and to alienate the very people on whom ultimately the success of the Service depends. Beneath the froth of wordy resistance to these proposals lies a very real fear of interference from any outside source between doctors and their patients. Nor is this a purely selfish fear, for the delicacy of the relationship between doctor and patient is something to which many people outside the profession can testify and which must be preserved if sympathetic understanding, as well as technical efficiency, is aimed at. It is on this fear that the real reactionaries within the profession play. This enables the B.M.A. to convey the impression that its members are united in their opposition to the Bill. Furthermore, this fear is not an unreasonable one if it is realised that in the past their contacts with the State have almost invariably involved them in distractions from their proper functions by endless regulations and certificates. If events were to justify this fear the Service will fall very gravely short of public expectations. Common Wealth has always maintained that Common Ownership has no virtue save as a means to an end. The same means can serve different ends, and just as nationalisation can be used for State capitalism, so a State Medical Service could turn a not ignoble profession into an army of squinting bureaucrats — one eye on the patient and the other on the chance of promotion. Not unless we admit that this could happen shall we be able to seek out and indicate the steps which are necessary to safeguard against it. 13 15X/2/98/21